Influence of social support, depression, and self-esteem on burden of care among caregivers of oncology patients (2009)
This study investigated the influence of social support, depression and self-esteem on the burden of care among informal caregivers of oncology patients. The cross-sectional correlational study included 278 informal oncology caregivers. Results showed a significant main effect of self-esteem (F(1,277) = 5.35; p<.05), and interaction effect of social support and depression (F(1, 277) = 4.86; p<.05) on caregivers’ burden. Caregivers with high level of depression (t=4.06, df=282, p<.001), and others with high levels of social support (t=4.06, df=282, p<.001) recorded significantly higher levels of caregivers’ burden. This suggests the need for improving the psychological well-being of informal caregivers of oncology patients in the expanding role of family community members in caring for cancer patients.